Interoperabilidade de dados em saúde: OpenFairEHR - um modelo conceitual no contexto dos princípios FAIR - Delfino, Samyr Santos (2023)
Issues related to the search for the best way to access and use data have become essential for contemporary society as a whole. In areas such as healthcare, the need for efficient use of data is evident, but technological advances that provide various benefits at the same time impose challenges that directly impact the sharing of this data. Examples of these challenges include the diversity of decentralized databases and the excessive amount of health data interoperability standards available. In this context, the main objective of the research consists of analyzing data interoperability, including the development of a conceptual model of data interoperability in healthcare. The methodological approach began with conducting an exploratory research on topics related to digital databases, metadata, interoperability, databases, and FAIR principles. Based on the initial stage, OpenEHR and FHIR standards were defined as reference standards. The FairDataBR tool was then chosen as the evaluation tool for the level of adaptability of reference standards with FAIR principles. Finally, the OpenFairEHR conceptual interoperability model was developed. The main results of the research involve identifying areas for improvement in the OpenEHR and FHIR standards regarding healthcare data interoperability, developing a conceptual interoperability model called OpenFairEHR. Finally, it was possible to identify that the use of the FAIR interoperability principles set independently of other FAIR elements is not recommended due to the existence of dependent requirements among these elements. Also, the joint use of OpenEHR and FHIR standards provides benefits in terms of healthcare data interoperability.